2021
DOI: 10.1200/jco.2021.39.15_suppl.e13557
|View full text |Cite
|
Sign up to set email alerts
|

To determine correlation of inter reader variability in sum of diameters using RECIST 1.1 with end point assessment in lung cancer.

Abstract: e13557 Background: Lung cancer is the leading cause of cancer death in the world including more than 160,000 deaths in the US. The purpose of the study was to determine whether inter reader variability in Sum of Diameters (SOD) of tumor burden has any correlation with variability in end point assessment in lung cancer progression. RECIST 1.1 is based on the SOD of target lesions seen on imaging studies. Response criteria for evaluation of target lesions include - Complete response (CR), Partial response (PR),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Our study confirmed findings by Sharma et al (31) who concluded that there was an association of the variability of SOD at baseline with the variability of the study endpoint. However, our percentage of specific sum of diameters (SPropSOD) analysis did not confirm or contradict other works about dissociated responses (28,32), probably because this phenomenon is reportedly observed in only around 10% of cases (28).…”
Section: Sum Of Diameters Valuesupporting
confidence: 92%
“…Our study confirmed findings by Sharma et al (31) who concluded that there was an association of the variability of SOD at baseline with the variability of the study endpoint. However, our percentage of specific sum of diameters (SPropSOD) analysis did not confirm or contradict other works about dissociated responses (28,32), probably because this phenomenon is reportedly observed in only around 10% of cases (28).…”
Section: Sum Of Diameters Valuesupporting
confidence: 92%
“…We know from Sharma et al. ( 16 ) that the variability in SOD at baseline is a risk for discrepant responses but, while threshold values for detecting significant longitudinal SOD changes (in follow up) are proposed ( 17 ), none are proposed for critical values for differences in SOD with double reads at baseline. Darkeh et al.…”
Section: Discussionmentioning
confidence: 99%